Power, Production and Social Reproduction
XIV, 250 p.
Keywords: Written by leading authorities from Europe, the Americas and Asia, this path-breaking work develops an innovative and original theorization of global political economy. Whilst most approaches theorize global political economy from the perspectives of power and production or states and markets, this work argues that what feminists call social reproduction is a more basic framework, upon which most forms of power and production, and states and markets, must necessarily rest. By combining Feminist and Radical Political Economy with Critical International Studies, the volume explores how global transformations of states, growth in the power of capital, and extension of market values and market forces in everyday life, all affect the security of the majority of the population, and the reproduction of communities and societies. The book shows how public and private forms of power regulate three main aspects of social reproduction: biological reproduction; reproduction of labour power; and social practices connected to caring and provisioning of human needs.